2008
DOI: 10.1186/1475-2875-7-165
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen misuses of bed nets in fishing villages along Lake Victoria

Abstract: Background: To combat malaria, the Kenya Ministry of Health and nongovernmental organizations (NGOs) have distributed insecticide-treated nets (ITNs) for use over beds, with coverage for children under five years of age increasing rapidly. Nevertheless, residents of fishing villages have started to use these bed nets for drying fish and fishing in Lake Victoria. This study investigated the extent of bed net misuse in fishing villages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 11 publications
4
110
1
Order By: Relevance
“…Since poverty remains high in rural areas of Uganda, the Government's strategy of free distribution of ITNs is likely to greatly benefit such communities. However, some studies conducted in other parts of Africa have shown misuse of received nets including being used for fishing 20,21 . Therefore, an all-encompassing approach including health education and targeting other malaria prevention methods is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Since poverty remains high in rural areas of Uganda, the Government's strategy of free distribution of ITNs is likely to greatly benefit such communities. However, some studies conducted in other parts of Africa have shown misuse of received nets including being used for fishing 20,21 . Therefore, an all-encompassing approach including health education and targeting other malaria prevention methods is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…15 Ensuring continued use entails a better understanding of LLIN user preferences, use patterns, alternative uses for LLINs, and factors influencing LLIN use. [16][17][18] Little data exist on sustained use of LLINs in regions of declining malaria transmission. LLIN use was evaluated over a 6-year period in a region of declining malaria transmission in southern Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…In major fishing villages in western Kenya, a considerable number of ITNs were used for catching and drying fish [14]. In Ethiopia, some people used ITNs for drying grain, tying cattle to a tree, and tablecloths, etc.…”
Section: Introductionmentioning
confidence: 99%